(3cJGH aj Gdabgs - (3eLghds ((3MSjf GdeMdGJjs)
(3ChdgG (B:s
... (3Ef Lgd MGdg PchQI hCfhKI hEf Yde MGdg PcQ CcGf Ch CfKi cGf GdOjI GdLfjf (B... (3Cda OjfGQ Ydi GdGhd hfUag Ydi GdKGfj HdG NdGa aj GdCLfI aUGQ aJhi hYdi GdCXgQ GdChd CjVG hgh GdCTgQ (B...s
(3BNQgG (B:s
... (3bGd hde CYOJe CdHS bO GfUQa QShd Gddg ajg Ke aj QcYJjf aCJe HQcYJjf EdG CJege hUMNI Ydi Hf CMeO GdQGRj GdKbI aCOQcJ eY CUMGH dj hCfG GeGege aUdjJ eYge GdeZQH (B...(3gPG BNQ eG GhQOfGgs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis